Transported smoke from crop residue burning as the major source of organic aerosol and health risks in northern Indian cities during post-monsoon - Yufang Hao; Jan Strähl; Peeyush Khare; Tianqu Cui; Kristty Schneider-Beltran; Lu Qi; Dongyu Wang; Jens Top; Mihnea Surdu; Deepika Bhattu; Himadri Sekhar Bhowmik; Pawan Vats; et al. (Environment International)
Ambient particulate matter significantly impacts air quality, climate, and human health. In the Indo-Gangetic Plain (IGP), home to nearly one-seventh of the global population, severe air pollution is prevalent with high PM2.5 levels dominated by organic aerosols (OA). However, the sources and formation of OA pollution remain poorly constrained. For the first time, we characterize OA sources in two cities, Delhi and Kanpur in the IGP, over an entire year by combining near-molecular characterizations using an extractive electrospray ionization time-of-flight mass spectrometer (EESI-TOF) with advanced statistical approaches. We identified three key local biomass burning sources—affected by various fuels such as wood, straw, and cow dung—that had a more pronounced impact on Kanpur (66 %) compared to Delhi (35 %), particularly during colder months. Additionally, we identified transported agricultural fire emissions from Northwest India, which significantly contributed to OA during the post-monsoon rice harvest season, playing a critical role in haze formation. Acute mortality estimates indicated that while urban OA sources were substantial, rural crop residue burning posed a notable health risk during the post-monsoon, accounting for 32 % of PM2.5-attributable mortality in Delhi and 53 % in Kanpur. These results highlight the need for coordinated air pollution mitigation strategies that extend beyond urban centres to a regional scale, with a particular focus on crop residue management in Punjab to reduce the health burden of PM2.5 pollution in the IGP.